2004
DOI: 10.1007/s10593-005-0098-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the products of interaction of cyclic diketones with nitrogen-containing 1,4-binucleophiles

Abstract: In cyclic 1,5-diketones the position of the carbonyl groups determines exclusively the ease of their cyclization and makes them as convenient basis for the synthesis of nitrogen-, oxygen-, and sulfur-containing heterocycles [1,2].The aim of the present work is the study of the reactivity of the Michael adducts 1a-j [3,4], obtained from dimedone and aromatic aldehydes or furfural (adduct 1j), in relation to the bidentatic nucleophiles o-phenylenediamine 2 and o-aminophenol 3. The cyclic tetraketones 1a-j exist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Earlier, 7 we have demonstrated that the reaction of aryl(aroyl)[bis(5,5 dimethyl 1,3 dioxocyclohexan 2 yl)]methanes with o phenylenediamine (o PDA) produces hexahydrobenzo[b,e] 1,4 diazepin 1 one derivatives 1A or 9 aryl(aroyl) 10 (2 aminophenyl)decahydroacridine 1,8 dione derivatives 2 depending on the electronic char acter of the substituent in the aryl or aroyl fragments. Electron withdrawing substituents in the aromatic moi ety facilitate the formation of the diazepine ring, whereas the formation of acridones is typical of the starting polyketones containing electron releasing substituents in the benzene ring.…”
mentioning
confidence: 99%
“…Earlier, 7 we have demonstrated that the reaction of aryl(aroyl)[bis(5,5 dimethyl 1,3 dioxocyclohexan 2 yl)]methanes with o phenylenediamine (o PDA) produces hexahydrobenzo[b,e] 1,4 diazepin 1 one derivatives 1A or 9 aryl(aroyl) 10 (2 aminophenyl)decahydroacridine 1,8 dione derivatives 2 depending on the electronic char acter of the substituent in the aryl or aroyl fragments. Electron withdrawing substituents in the aromatic moi ety facilitate the formation of the diazepine ring, whereas the formation of acridones is typical of the starting polyketones containing electron releasing substituents in the benzene ring.…”
mentioning
confidence: 99%
“…The composition and structure of diazepinones 5a-r have been proved via elemental analysis, 1 H, 13 C NMR spectroscopy and in some cases mass spectrometry data. The presence of molecular ion peaks of low intensity and also fragmentary ion signals corresponding to the masses of dibenzodiazepine (highest in intensity) and aroyl fragments was common for all mass spectra of hexahydrodibenzo [b,е] The signals of all proton-containing fragments are present in 1 H NMR spectra of compounds 5a-p.…”
Section: Resultsmentioning
confidence: 99%
“…The methylen proton and iminogroup proton in diazepinones 5a-r interact with each other which leads to a doublet in the spectra (J 5.0 Hz). In 13 C NMR spectra of compounds 5e,f,h-j,m all the necessary carbon signals are present, and using the DEPT-135 procedure allows us to identify the signals of secondary and tertiary carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations